Legal Policy of Forest Management in Indonesia through Local Wisdom and Traditional Ecological Knowledge - Rohmy, Atikah Mardhiya; Sunarjo (Fakultas Syariah INSURI Ponorogo, 2025)
The purpose of this study is to examine forest management laws from a local wisdom perspective, with the goal of protecting biodiversity and maintaining the functions of forest ecosystems. Therefore, effective local wisdom legal policies are needed to improve sustainable forest management in Indonesia. A literature review is the research methodology employed to explore literature related to good forest governance and forestry legal policy in Indonesia. The results of this study indicate that the existing legal framework often fails to guarantee the equitable distribution of resources, the recognition of indigenous peoples' rights, substantial public involvement, and skills improvement across all ecosystem components. Due to regulatory uncertainty, tenurial disputes between local communities and indigenous peoples persist, often involving government agencies and businesses, and public involvement remains limited. Awareness and recognition of the inseparable interaction between organisms and their surroundings underscore the importance of traditional ecological knowledge in emphasizing the unity of all elements that live, grow, and develop together on planet Earth. For this reason, a local wisdom legal policy construction model is needed that describes how to care for forests and natural resources connected to the landscape through a Co-management model by synergizing and integrating Traditional Ecological Knowledge (TEK) into forest management policies.